Dependability Analysis of the Injection Press Using Weibull Distribution - Michalkova, Petra; Legat, Vaclav; Ales, Zdenek (Manufacturing Technology Journal, 2018)
The aim of this paper is an analysis of dependability of an injection press. Collected data - operating times between failures and times to restoration for a year of the use of the press were processed using the Weibull distribution, for which the following basic steps were applied in compliance with CSN EN 61649:2009 standard. The output includes Weibull distribution parameters and basic functions of reliability and maintainability, i.e. probability of failure and of reliability, density and intensity of failures, then also probability of restoration and restoration probability density. Last but not least, mean time between failures and mean time to restoration including steady-state availability were calculated. The results obtained can be useful for internal benchmarking in an organization with a higher number of presses and for developing a maintenance strategy.
Keywords: Dependability; Weibull distribution; injection press